2016
DOI: 10.1021/acs.macromol.6b00180
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Grafted Ion-Conducting Membranes: The Influence of Variations in Base Film Nanostructure

Abstract: The proton exchange membrane (PEM) is a key element of a polymer electrolyte fuel cell, and radiation-grafting is an attractive option for the synthesis of PEMs. Via a systematic investigation of a well-defined model material, sulfonated polystyrene grafted poly(ethylene-alt-tetrafluoroethylene), ETFE-g-PS(SA), we show that the performance and stability of radiation-grafted PEMs in fuel cells strongly depends on the microstructure of the underlying base polymer. The nanoscale structure of the base polymers, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 65 publications
8
35
0
Order By: Relevance
“…This is a dramatic demonstration of the findings by Sproll et al related to the development of RG-proton-exchange membranes (RG-PEM), 12 who reported that conductivities, water uptakes, and resulting fuel cell (PEMFC) performances strongly depend on the micro-structure of the ETFE-base films used. The use of nominally identical base ETFE films (from two suppliers), differing only in microstructure, resulted in critical differences in the final membranes: larger crystalline sizes led to enhanced RG-PEM conductivities and durabilities of the resulting PEMFCs.…”
supporting
confidence: 56%
“…This is a dramatic demonstration of the findings by Sproll et al related to the development of RG-proton-exchange membranes (RG-PEM), 12 who reported that conductivities, water uptakes, and resulting fuel cell (PEMFC) performances strongly depend on the micro-structure of the ETFE-base films used. The use of nominally identical base ETFE films (from two suppliers), differing only in microstructure, resulted in critical differences in the final membranes: larger crystalline sizes led to enhanced RG-PEM conductivities and durabilities of the resulting PEMFCs.…”
supporting
confidence: 56%
“…The corresponding characteristic distances are quite similar for both PEMs, which reflects that the swelling of the base film is due to the grafted polymer . This characteristic distance is, however, slightly larger for the L‐PEM (approx.…”
Section: Resultsmentioning
confidence: 76%
“…15 wt% with an average crystallite size of approx. 9 nm . To enhance scattering from the ionic groups located exclusively in the grafted domains, both PEMs were converted into the Cs‐salt form as outlined in ref .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This radiation technique allows us to introduce various functional grafted polymers directly bonded to the main chains of polymer substrates, while the inherent characteristics of the polymer substrates such as thermal stability, mechanical strength, and crystallinity are still retained. Morphology of the graft‐type PEMs prepared by the above radiation grafting technique has been intensively investigated using the small‐angle scattering methods with various matrix polymers of poly(tetrafluoroethylene) (PTFE), poly(ether ether ketone) (PEEK), poly(vinylidene fluoride) (PVDF), and poly(ethylene‐ co ‐tetrafluoroethylene) (ETFE) . Consequently, various general features have been well‐established as follows.…”
Section: Introductionmentioning
confidence: 99%